Towards Trust Establishment for Spectrum Selection in Cognitive Radio Networks - Parvin, Sazia; Han, Song; Gao, Li; Hussain, Farookh Khadeer; Chang, Elizabeth (IEEE Computer Society, 2010)
Cognitive Radio (CR) has been considered as a promising concept for improving the utilization of limited radio spectrum resources for future wireless communications and mobile computing. As cognitive radio network (CRN) is a general wireless heterogeneous network, it is very essential for detecting the misbehaving or false nodes in the network. So in this paper we propose a trust aware model which provides a reliable approach to establish trust for CRN. This approach combines all kinds of trust values together, including the direct trust and indirect trust value for the secondary users. Depending on this trust value, it is decided that whether the secondary user can user the primary user's spectrum band or not. The mathematical results show that our trust model can efficiently take decision for assigning spectrums to the users.